Household Electrical Power Meter Using Embedded Rfid With Wireless Sensor Network Platform - Boonsong, Wasana (2016)
Smart monitoring utility electrical power meter plays an important role in the energy awareness scheme. The aim of this study is to develop a machine-to-machine (M2M) communication by embedding an active RFID technology with wireless mesh sensor network (WMSN) platform with heterogeneous data transfer to monitor and identify the household electrical consumption. A household electrical power meter is designed with chosen Zigbee-Pro as a RF transceiver module with WSN functionalities to communicate between RFID tag to the RFID reader wirelessly. The development of this project involves three main parts in the proposed RFID communication system which consists of: the EPRFID (embedded RFID module with household electrical power meter), reader and application software at a work station. The EPRFID module is designed to take power supply from a household electric power meter with the introduction of power management circuit developed inside the proposed module. It comprises of voltage and current sensors which is functioning to precisely sense the actual status of the resident electrical power consumption from the appliance loads. Then, the data signal is directly transferred to the central processing unit (CPU) to precisely calculate the current power consumption. The CPU is the central part to effectively communicate and command all defined operations. The real time clock is readily available to generate the local real time clock. It is combined into the memory module package which used to minute the total accumulated power. Simultaneously, the display unit shows the monitored information data such as local time, current, voltage and power values. Lastly, the application software at a personal computer (PC) was designed by using the Microsoft Visual C# software. It shows the performances of received information data from the end meter devices such as tag ID, time sent, receive, delay, accumulated power, RSSI and amount of received bytes. In this research, the EPRFID prototype was intensively examined as follows: the voltage and current calibration versus the distance ranges; the transmitted power calibration; energy analysis; energy tradeoffs based on measured dc characteristics; anti collision performance; radiation pattern; maximum read range; tag collection and latency delay time; throughput evaluation. The experimental results indicated that the proposed EPRFID prototype successfully worked wirelessly with tolerable power consumption is within a range of 1.61 W to 1.69 W. This model is to facilitate some daily life processes, saving time, and reduces the operating cost because of the reduction in the manpower requirement and error in information system that can be omitted through humans. Thus, improving the M2M communication can provide higher reliability on the communication system because the current development will focus on local control strategies. In addition, this study can be guidelines to the electrical power utility company and consumers for alternatives in electrical consumption billings in the future.